2017
DOI: 10.1002/itl2.8
|View full text |Cite
|
Sign up to set email alerts
|

Outage analysis of nonorthogonal in‐band relay‐aided device‐to‐device communications in Rayleigh fading channels

Abstract: Minimizing the outage probability and/or maximizing the throughput, optimally realize relay‐aided nonorthogonal in‐band (NO‐IB) device‐to‐device (D2D) communications. In this letter, we derive closed‐form expressions for the outage probability of NO‐IB amplify‐and‐forward (AF) and decode‐and‐forward (DF) relay‐aided D2D communications in Rayleigh fading channels. Numerical analyses show that the closed‐form formulas are in close agreement with the simulation results. Furthermore, we investigate the effect of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the first one, regarding the signal quality, minimizing the outage probability and in the second one, in view of the traffic and the desired throughput, maximizing the throughput can be achieved. In an in-band underlay manner, in addition to considering the noise effects and multi-path fading phenomenon, it is necessary to add the effect of interference arising from the reused radio resources [37,38]. With the help of fixed or mobile relay nodes, the distance between the transmitter and receiver nodes of a D2D pair increases and the quality of service (QoS) improves.…”
Section: D2d Communicationsmentioning
confidence: 99%
“…In the first one, regarding the signal quality, minimizing the outage probability and in the second one, in view of the traffic and the desired throughput, maximizing the throughput can be achieved. In an in-band underlay manner, in addition to considering the noise effects and multi-path fading phenomenon, it is necessary to add the effect of interference arising from the reused radio resources [37,38]. With the help of fixed or mobile relay nodes, the distance between the transmitter and receiver nodes of a D2D pair increases and the quality of service (QoS) improves.…”
Section: D2d Communicationsmentioning
confidence: 99%
“…Recently, Ref. [11] derived two closed-form expressions for the outage probability of non-orthogonal in-band AF and DF relay-aided D2D communications in Rayleigh channels. According to the numerical analyses of this investigation, it was indicated that in the low-noise regime, AF outperforms DF while they perform very close to each other in the moderate noise level and DF outperforms AF in the high-noise power.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the obtained low-complex closed-form expressions are just valid for high-enough SINRs. In addition, it is clear that the formulations and results of [11] are not applicable for relay-aided D2D communications in Nakagami fading channels and does not exist any low-complex outage probability expression for the DF relay-aided D2D communications appropriate for all SNRs in a Nakagami fading channel.…”
Section: Introductionmentioning
confidence: 99%